Analisis Jaringan Pemasaran Produk Perikanan Dan Dampaknya Terhadap Pendapatan Pembudidaya Ikan Di Waduk Darma Kabupaten Kuningan - Dede Nishfi; Junianto Junianto (Universitas Mataram, 2024)
This study analyzes the marketing network of fishery products and its impact on fish farmers' income in Darma Reservoir, Kuningan Regency. The reservoir is a significant center for freshwater aquaculture in West Java, yet fish farmers face challenges such as price fluctuations, limited market access, and uneven marketing margins. A qualitative approach was employed through participatory observation and in-depth interviews with fish farmers, traders, and stakeholders. The study identified three main marketing patterns: direct sales to consumers, sales through collectors and retailers, and longer chains involving wholesalers. The most influential factors affecting farmers' income are business scale and market access. The efficiency of marketing networks significantly impacts income. The study recommends strategies such as institutional strengthening, development of market information systems, product diversification, quality improvement, and broader market access facilitation to enhance fish farmers' welfare